Manajemen Talenta Sumber Daya Manusia Pendidikan Islam di SDIT Ash Haabul Kahfi Lubuk Alung - Nasrin Hasibuan; Zulfani Sesmiarni; Ali Mustopa Yakub Simbolon (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Talent management is a crucial element in human resource (HR) management in Islamic educational institutions to achieve optimal education quality. This study aims to examine the HR talent management process in Islamic educational institutions with a focus on aspects of recruitment, development, spiritual and moral guidance, performance evaluation, career development, and talent identification. The research method used is quantitative descriptive with data collection through questionnaires distributed to 30 educators and staff in Islamic educational institutions. The results of data analysis show that the talent management process has been carried out effectively, with an average score above 4.0 for all aspects analyzed. This study recommends improving the evaluation system and spiritual guidance as the key to sustainable HR development in Islamic education.